Front desk technology innovation in hotels: A managerial perspective. (October 2019) - Shin, Hakseung; Perdue, Richard R.; Kang, Juhyun
Abstract: Understanding technology innovation is a key strategic management concern in hotels. Still, the existing hotel technology research has focused heavily on technology adoption processes; even though technology adoption is mandatory for most employees. There is a lack of scholarly knowledge of the company-wide managerial processes and effects associated with technology innovation. To fill this research gap, using Helkkula et al.'s (2018) service innovation archetypes as a theoretical lens, this research explored the effects associated with hotel front desk technology innovation by a large multi-national hotel corporation. Following a qualitative approach, written interviews of 251 hotel managers were conducted. Three-step thematic analysis was used to examine the data. Specifically, the sequential hiring, training, and implementing process associated with technology innovation, the outputs of technology innovation, and experiential value were examined to develop a comprehensive operational framework. The framework provides strategic knowledge on successful development and management of front desk technology. Highlights: A holistic managerial framework for understanding the effects of front desk technology innovation was developed. Hotel front desk technology innovation affects operational processes, output, experiences, and systems. Front desk technology innovation influences human resource management practices including hiring and training. Front desk employees can be more effective in their tasks when they use the innovative front desk technology. Front desk technology innovation leads to "high-touch and high-tech" and "personalized" service experiences.